Study of Multi-Drug Resistance Associated with Anti-Tuberculosis Treatment by DOT Implementation Strategy in Pakistan - Sana Saeed; Moosa Raza; Maryam Shabbir; Muhammad Furqan Akhtar; Ali Sharif; Muhammad Zaman; Sajid Ali; Sajid Nawaz; Ayesha Saeed (Journal of Basic & Applied Sciences, 2018)
Purpose: The present prospective cross sectional study was aimed to access the prevalence and trend of Multi-Drug Resistant Tuberculosis (MDR-TB) in different age groups and gender, in the city of Lahore, Pakistan. Tuberculosis is a disease of poverty affecting mostly young adults in their most productive years; however, all age groups are at risk. Method: The study population consisted of patients under DOT program with MDR-TB among males and females and in different categories of age groups. The data was collected from 100 MDR-TB patients from 7800 TB patients that were admitted in duration of 6 months and analyzed to evaluate the drug resistance associated with patient’s noncompliance. Moreover, drugs resistance ratio was also calculated from the data. Results: TB is a specific infectious disease, caused by M. tuberculosis strains, which is becoming resistant to anti-tuberculosis agents especially to Isoniazid and Rifampicin that are two key drugs of TB treatment and are termed as MDR-TB. The disease was seen in 66% males and 34% in female. The highest drug resistance ratio was in found in adults (age group).